수부손상환자 진료비에 미치는 영향요인 -서울시 소재 S병원의 환례를 대상으로 - 양재영; 서원식; Yang, Jae-Young; Suh, Won-S (한국콘텐츠학회 논문지, 12(4), 2012)
This study aims to argue fundamental issues on factors associated with revenues of hand injury patients to effectively manage hospitals specialized in hand injuries. The study employes 2,461 patients who entered S hospital from 2008 to 2010 with hand injuries. The followings are the results of the study. First, there is significant difference among occurrence of hand injuries with regard to demographics of patients. That is, it is likely to have longer average length of stay(ALOS) of male over female, of the elderly over infants and toddlers, and vice versa on average daily patient revenues. Also, compared to patients with traffic and labor insurance, patients with health insurance is likely to stay longer at lower daily cost. Fifth, demographics and incidence of hand injuries were significantly associated with average length of stay(ALOS) and average daily patient revenues. That is, male over female, age over 60 over any other age categories, patients with traffic and labor insurances over one with health insurance, cases with laceration, avulsion and bone transplantation over any other types of hand injury patients were factors significantly related to ALOS and average daily patient revenues. In sum, it is needed to focus on education and campaign to raise attentions on preventing various hand injuries. Also, managers at hospitals specialized in hand injuries should pay attention on issues such as reducing ALOS to run the organization effectively. 이 연구는 수부손상의 발생요인과 진료양상을 분석함으로써 수부손상의 예방과 수부전문병원의 진료 효율성 제고를 위한 기초정보를 제공하기 위해 수행되었다. 분석을 위해 서울시 소재 S병원에 2008년 1월 1일부터 2010년 12월 31일까지 최근 3년간 내원한 환자 중 수부손상 환자 총 2,461명의 환례를 전수 조사 하였다. 분석결과는 다음과 같다. 첫째, 수부손상 환자의 인적특성군 별로 수부손상 발생의 시기, 장소, 원인별 빈도와 유의한 차이를 보였다. 남자가 여자에 비해, 노년기환자가 영유아기환자에 비해 재원기간은 긴 반면 일평균진료비는 낮았으며, 국민건강보험환자가 자동차보험과 산재보험환자에 비해 재원기간은 짧은 반면 일평균진료비는 높았다. 둘째, 수부손상 환자의 인적특성변수와 수부손상의 발생양상변수는 재원기간과 일평균진료비, 건당 평균진료비에 유의한 영향을 보였다. 수부손상환례의 재원기간이 건당진료비의 크기를 결정하는 요인이기 때문에 재원기간에 정(正)의 영향을 미치거나 재원기간에 유의한 차이가 있는 남성, 노년기, 산재보험환자의 기계 작업도구에 의한 환례, 절단 결출상의 환례, 그리고 이식술의 재원기간을 단축하는 방안이 치료 효율을 위해 긴요한 것으로 보인다. 이에 수부손상환례의 조속한 진단 치료로 재원기간 단축 등을 통해 수부전문병원의 진료효율성 제고방안을 다양한 차원에서 강구할 것을 제언한다.